ЕРИТРОПОЕТИН ЯК НЕЗАЛЕЖНИЙ ПРОГНОСТИЧНИЙ ФАКТОР У ХВОРИХ НА МІЄЛОДИСПЛАСТИЧНІ СИНДРОМИ - Boyko, O.; Simonova, M.; Knysh, N.; Danysh, O.; Vygovska, Y.; Masliak, Z. (PH Akademperiodyka, 2023)
Aim: To assess the level of erythropoietin (EPO) in blood sera of patients with different subtypes of myelodysplastic syndromes (MDS) from different risk subgroups and to determine its prognostic role. Materials and Methods: EPO was measured by enzyme-linked immunosorbent assay in peripheral blood of 54 patients with different MDS subtypes according to the French–American–British (FAB) classification. The comparison group consisted of 15 healthy individuals. Complete blood count (hemoglobin, leukocyte and platelet levels) was determined and bone marrow cells were characterized morphologically. The overall and leukemia-free survivals were estimated by Kaplan — Meier method. Results: The level of ЕРО in MDS was reliably higher in comparison with healthy persons (p < 0.01, Mann — Whitney test). No statistically significant difference was found in serum EPO concentration between the groups of patients with low- and high-risk MDS (603.5 pg/ml vs 721.0 pg/ml; p > 0.05). In transfusion-dependent patients, the level of EPO was significantly higher than in other patients, which may be due to increased endogenous EPO secretion resulting from chronic hypoxia. A negative correlation was revealed between EPO level and Hb level as well as between EPO level and percentage of blast cells in bone marrow in high-risk MDS patients but not in patients with less aggressive variants of MDS. Instead, patients with low-risk MDS had a negative relationship between concentrations of EPO and tumor necrosis factor alpha (p = 0.06, Kendall’s tau test). No significant difference was found between EPO concentration in cases differing by bone marrow cellularity or the presence of cytogenetic abnormalities. An EPO concentration below 200 pg/ml was a predictor of shorter overall survival in patients with all MDS subtypes (p < 0.05, Mann — Whitney test). In patients with all FAB disease subtypes, there was no relationship between the leukemia-free survival and serum EPO concentration. Conclusion: This study shows that lower serum EPO level may be considered as one of the additional adverse prognostic factors in MDS patients.